1998
DOI: 10.1017/s1357729800010109
|View full text |Cite
|
Sign up to set email alerts
|

The influence of litter size on milk production of sows

Abstract: Thirty sows were allocated at their first farrowing to five litter size treatments. Litter sizes of six, eight, 10,12 and 14 were established by cross-fostering within 48 h post partum. Milk yield (Y, kg/day) of sows was linearly related to litter size (L) and was described by the equations; Y = 5-98 (s.e. 0-48) + 0-689 (s.e. 0-046)L, R 2 = 0-99; residual s.d. = 0-29; P < 0-001 and Y = 8-20 (s.e. 0-46) + 0-324 (s.e. 0-044)1, R 2 = 0-95; residual s.d. = 0-28; P < 0-002 for early (day 10 to day 14) and late (day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 12 publications
7
43
1
4
Order By: Relevance
“…In line with this, Auldist et al (1998) found a decrease in average growth rate of piglets until weaning when litter size increased from 6 to 14.…”
Section: Implications For Piglets Due To Larger Litter Sizesupporting
confidence: 72%
See 1 more Smart Citation
“…In line with this, Auldist et al (1998) found a decrease in average growth rate of piglets until weaning when litter size increased from 6 to 14.…”
Section: Implications For Piglets Due To Larger Litter Sizesupporting
confidence: 72%
“…As production of colostrum is not influenced by litter size, less colostrum is provided per piglet in larger litters (Devillers et al, 2007). And even though milk production in total increases as litter size increases (Auldist et al, 1998;Kim et al, 1999;King, 2000), milk intake per individual piglet also decreases in large litters (Kim et al, 1999;King, 2000).…”
Section: Implications For Piglets Due To Larger Litter Sizementioning
confidence: 99%
“…Contrary to what is seen with milk production (Auldist et al, 1998), litter size did not affect colostrum yield, thereby confirming the absence of a litter size effect on piglets' growth during the first postnatal days (Milligan et al, 2001;Le Dividich et al, 2004). Piglets from larger litters therefore have less colostrum available on an individual basis.…”
Section: Figurementioning
confidence: 63%
“…As piglets born to G1 L and G1 N mothers grew at approximately the same rate, it is likely that milk production may have been greater in the G1 N animals as they reared more young. There is a strong litter correlation between milk yield and litter size and it has been proposed that sows are capable of producing higher yields in early lactation if more milk is removed (Elsley et al, 1971;Auldist et al, 1998;King, 2000).…”
Section: Discussionmentioning
confidence: 99%